Return to Play and Performance After Anterior Cruciate Ligament Reconstruction in the National Women's Soccer League. Issue 5 (2nd May 2023) - Abed, Varag; Dupati, Ajith; Hawk, Gregory S.; Johnson, Darren; Conley, Caitlin; Stone, Austin V.
Background: The anterior cruciate ligament (ACL) is commonly injured in elite-level female athletes, which usually requires ACL reconstruction (ACLR). Purpose: To analyze return to play (RTP) and changes in performance of players in the National Women's Soccer League (NWSL) after ACLR. Study Design: Descriptive epidemiology study. Methods: NWSL players who sustained an ACL tear and underwent surgery between the 2013 and 2020 seasons were identified by multiple online resources. Players were classified as forwards, defenders, midfielders, and goalkeepers. RTP was assessed according to games played, games started, percentage of minutes played, plus/minus net per 90 minutes (a measure of a player's contribution to their team's performance while on the field), goals scored, and assists. A subanalysis was performed based on the median age at the time of the injury (≤24 vs ≥25 years). Nonparametric testing methods were used throughout the analysis. Results: A total of 30 NWSL athletes were included. Midfielders had the highest percentage of injuries (n = 11; 36.7%), followed by forwards (n = 10; 33.3%). Overall, 27 players returned to the NWSL at a median of 12.1 months (IQR, 10.9-14.3 months), constituting a 90.0% RTP rate. There was a significant decrease in the percentage of minutes played from 1 year before the injury to 1 year after the injury (median, 87.9% [IQR, 80.7%-90.6%] vs 25.1% [IQR, 16.3%-57.2%], respectively; P = .031). Forwards and midfielders had a significant decrease in the number of assists from 1 year before the injury to 1 year after the injury (median, 3.0 [IQR, 1.0-3.0] vs 0.0 [IQR, 0.0-1.0], respectively; P = .037) as well as the number of goals scored when averaging across 2 seasons before the injury to 2 seasons after the injury (median, 3.0 [IQR, 1.5-5.5] vs 1.0 [IQR, 0.5-3.5], respectively; P = .031). On subanalysis, older players started in significantly more games (median, 12.0 [IQR, 3.8-18.5] vs 3.0 [IQR, 0.5-6.0], respectively; P = .048) and had a higher percentage of minutes played (median, 63.0% [IQR, 18.8%-77.3%] vs 14.9% [IQR, 2.0%-21.2%], respectively; P = .046) at 1 year after the injury versus younger players. Conclusion: There was a 90.0% RTP rate after ACLR in the NWSL. Players who returned to the NWSL had a lower percentage of minutes played in their first year after RTP, with older players starting in more games and having a greater percentage of minutes played. Compared with preinjury performance, forwards and midfielders had a significant decrease in the number of assists at 1 year after the injury as well as the number of goals scored at 2 years after the injury.